MODAL AND THERMAL-MECHANICAL COUPLING ANALYSIS INAUTOMOTIVE DISC BRAKE MECHANISM - BI HouHuang; HE JiaNing; LI ShiJin; GUO Kai (Jixie qiangdu)
Brake pad is vibrating when it is friction contact with the brake disc surface in automotive disc brake mechanism.When the vibration rate is close to its natural frequency of the material. It is easily lead to unobvious craze and collapse in slice body structure. The natural frequency and the temperature field and the thermal field generated by the friction action of the brake disc are different from various pad material. Through the modal analysis of the disc brake pad in different material parameters,and use the ABAQUS to analyze the display dynamic thermal mechanical coupling in brake mechanism. Take the output results of the brake pad natural frequency and the brake disk node temperature,displacements,thermal stress compare with others. The data shows that the composite brake pad is better than the half metallic materials during brake process in avoid resonance and improve braking performance sides. The comprehensive analysis results and solutions,It has reference value in improving safety and brake efficiency aspects about the brake mechanism.